Goldilocks Principle: Preference for Change in Breast Size in Breast Cancer Reconstruction Patients - Nicklaus, Krista M.; Bui, Thao; Bordes, Mary Catherine; Liu, Jun; Chopra, Deepti; Hoffman, Aubri S.; Reece, Gregory P.; Hanson, Summer E.; Merchant, Fatima A.; Markey, Mia K. (Frontiers in Psychology, 2021)
Patients’ preferences regarding changing or maintaining their breast size after mastectomy and reconstruction are important but understudied determinants of post-surgical satisfaction and quality of life. The goal of this study was to identify factors associated with preferences for changing or maintaining breast size for women undergoing breast reconstruction at The University of Texas MD Anderson Cancer Center in the United States from 2011-2014. The average age of participants was 45.7 ± 9.1 years. At baseline, mean average breast volumes were 755.7 ± 328.4 mL for all women (n = 48), 492.3 mL ± 209.3 for 13 women who preferred to be “bigger than now”, 799.2 mL ± 320.9 for 25 women who preferred to remain “about the same”, and 989.3 mL ± 253.1 for 10 women who preferred “smaller than now”. Among the 23 women who preferred to change their breast size, 19 desired to shift towards the mean. Women with the smallest and largest 20% of baseline breast size were more likely to desire a change towards the mean (p = 0.006). Multinomial logistic regression models found average breast volume and satisfaction with breast size to be the most important factors associated with preferences for changing or maintaining breast size for women undergoing breast reconstruction. This study provides preliminary evidence for a "Goldilocks principle" in women’s preferences for breast size change in the context of breast reconstruction, and identifies hypotheses for future studies of the associations among preference for change in breast size, preference achievement, and post-reconstruction body image.